On the interaction of sustrate analogues with non-phosphorylating glyceraldehydes-3-phosphate dehydrogenase from celery leaves - Iglesias, Alberto Alvaro (2002)
Structural analogues of D-glyceraldehyde-3-phosphate (D-Ga3P) and NADP+ were studied as potential substrates and inhibitors of the non-phosphorylating glyceraldehyde-3-phosphate dehydrogenase (EC 1.2.1.9; GAPN) from Apium graveolens leaves. Four analogues of NADP+: nicotinamide-hypoxanthine dinucleotide phosphate (NHDP+); 3-acetylpyridine-adenine dinucleotide phosphate (APADP+); 1,N6-etheno-nicotinamide dinucleotide phosphate (oNADP+); and b-nicotinamide adenine dinucleotide 2´:3´-cyclic monophosphate (2?3?NADP+c) were alternative enzyme substrates, with a 2-fold variation in Vmax and 2+/11-fold differences in Km compared to NADP+. These compounds were also able to affect the hysteretic behavior of celery GAPN, in a similar way as the substrate NADP+. The analogues to the nicotinamide moiety: thionicotinamide and 3-aminopyridine, behaved as competitive inhibitors, exhibiting a high-affinity binding to the enzyme. All the analogues of D-Ga3P that were analyzed behaved as competitive inhibitors, except for the L-isomer of the substrate which at relatively high concentrations exhibited a non-competitive effect. Results showed the importance of: (i) the chemical group at carbon-1 of Ga3P; (ii) the presence of a phosphate ester at carbon-3, and (iii) the stereochemical configuration at carbon-2. The particular behavior of L-Ga3P is analyzed by differences in tridimensional structure between bacteria and plant GAPNs.